Verdi's Aida - Ghislanzoni, Antonio, 1824-1893 (Opera classics library., 2005)
A comprehensive guide to Verdi's AIDA, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with ItalianEnglish side-by side, and over 30 music highlight examples.